Leave Management System (LMS) / Lee Chun Hoo - Lee, Chun Hoo (2000)
This project is carried out based on the study of the Leave Management System (LMS) in Faculty of Science Computer and Information Technology (FSCIT). The study shows that the above system implemented in FSCIT is inefficient and most of the documents are not well organized. Therefore a further study has been done to determine the feasibility of the LMS in FSCIT. At the end of this report, it is clear that, by computerizing the existing leave application process through the business process reengineering, overall performance will be boosted and it will help to promote a paperless environment, revolutionizing the way of how the office operates. Leave Management System proposed in this project is a Web based application. It is designed to suite the requirements of the current systems in FSCIT and is now being implemented in FCSIT. Literature review has been carried out to select the most suitable tools for the proposed system. Besides, recommendations of changes, problems faced, the design and implementation of the system as well as the comparisons of the current with the proposed systems are discussed.